(untitled) (Journal of Environmental Science and Natural Resources, 2016)
A field experiment was conducted at the experimental field of the Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during November 2013 to March 2014. Four soybean genotypes i.e BU Soybean1, BD2329, BD2331, AGS313 and a check variety BARI Soybean 6 were used to evaluate their variations in morphological characters and yield attributes. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. The highest LAI (4.4) was found in genotype AGS313 and the smallest was found in BU Soyabean1. The highest pod size of 625 mg pod-1 was found in AGS313 while the lowest of 340 mg pod-1 was observed in BU Soybean1. Although BU Soyabean1 had smaller seed size but it had higher number of pods plant-1 (32.1) compared to other genotypes. The maximum 100-seed weight was recorded in AGS313 (16.34 g) and the minimum was obtained from the genotype BU Soybean1 (11.0 g). AGS313 genotype contributed to the highest grain yield of 4.29 tha-1, while BU Soyabean1 stood second position contributing 2.65 tha-1. Results also indicated that not only seed size but also number of pods plant-1 contributed to grain yield. Again there were highly significant differences among genotypes for all the characters. J. Environ. Sci. & Natural Resources, 8(2): 93-96 2015